Environment–economic Growth Nexus: A Comparative Analysis of Developed and Developing Countries - Acaravci, Ali; Akalin, Guray (International Journal of Energy Economics and Policy, 2017)
This study aims to examine the interaction between carbon emissions, income, and trade openness in developed and developing countries for the period from 1980 to 2010 by using recently developed panel data econometric methods. The results are as follows i) There is an evidence of the cross-sectional dependence for each variable. ii) The cross-sectionally augmented and Smith et al.’s panel unit root tests are indicate that all variables are stationary at their first difference. iii) A Durbin–Hausman cointegration test shows that there exists a long-term relationship between variables. iv) The results from the common correlated effect (CCE) estimator presents that there is evidence of the validity of the environmental Kuznets curve (EKC) hypothesis in developed countries. v) The EKC hypothesis is not valid in developing countries. Keywords: Economic Growth, Environmental Kuznets Curve, Panel Data Analysis JEL classifications: C33, O57, Q43, Q53, Q56